Room temperature bubble point, flow-through screen, and wicking experiments for screen channel liquid acquisition devices. (25th February 2019) - Camarotti, Chase; Deng, Oscar; Darr, Samuel; Hartwig, Jason; Chung, J.N.
Highlights: Performance data is presented for three influential factors used to design LADs. Bubble point pressure increases with increasing screen fineness. Flow through screen pressure drop is inversely related to void fraction. Wicking front velocity increases with decreasing screen fineness. Data from this paper increases the existing LAD screen influential factor database. Abstract: This paper presents fundamental performance data for three of the influential factors that are required to design, size, and analyze screen channel liquid acquisition devices (LADs) for future in-space cryogenic propulsion systems. Bubble point, flow-through-screen, and wicking rate experiments are conducted on 14 different screen meshes, including three different metals (steel, aluminum, titanium), two different diameter screen samples (1.25″ and 2.50″), using multiple room temperature fluids (acetone, isopropyl alcohol, and water). Emphasis in the current work is on coarser meshes where there is a lack of reliable data. Corresponding analytical models from Hartwig and Darr (2014) are updated for each of the three influential factors, including a new evaporation rate-corrected wicking rate equation. Data obtained from this experiment will allow for efficient and accurate computational fluid dynamics simulations for flow out of a storage tank using LADs with mesh screens.